2016
DOI: 10.1126/science.aad3108
|View full text |Cite
|
Sign up to set email alerts
|

Periodic slow slip triggers megathrust zone earthquakes in northeastern Japan

Abstract: Both aseismic and seismic slip accommodate relative motion across partially coupled plate-boundary faults. In northeastern Japan, aseismic slip occurs in the form of decelerating afterslip after large interplate earthquakes and as relatively steady slip on uncoupled areas of the subduction thrust. Here we report on a previously unrecognized quasi-periodic slow-slip behavior that is widespread in the megathrust zone. The repeat intervals of the slow slip range from 1 to 6 years and often coincide with or preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 41 publications
5
162
2
1
Order By: Relevance
“…Comparing between the results of different sub-time-windows, swath widths and components may help us to distinguish long-term non-tectonic deformation from the tectonic deformation. Recently, Uchida et al (2016) revealed the periodic changes in the interplate coupling in the NE Japan subduction zone based primarily on the activity of small repeating earthquakes. They found that slow slip on the plate interface had occurred repeatedly at intervals of 1-6 yr, depending on the location.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing between the results of different sub-time-windows, swath widths and components may help us to distinguish long-term non-tectonic deformation from the tectonic deformation. Recently, Uchida et al (2016) revealed the periodic changes in the interplate coupling in the NE Japan subduction zone based primarily on the activity of small repeating earthquakes. They found that slow slip on the plate interface had occurred repeatedly at intervals of 1-6 yr, depending on the location.…”
Section: Discussionmentioning
confidence: 99%
“…These events are usually attributed to the repeated rupture of small patches on a homogeneous and stably sliding background. There may exist a multiscale structure of stable patches behind them, but it would be difficult to observe this complex structure within the limited period of the seismic cycle (Uchida et al 2016). Nevertheless, the long-term observation of slip-deficit evolution and differences in amplitude for repeating events may provide further insight into the complex structure of the plate interface.…”
Section: Discussionmentioning
confidence: 99%
“…Most large interplate thrust earthquakes occurred in high-velocity areas that may represent high-strength asperities (Huang and Zhao 2013); In contrast, a low-velocity area associated with abundant sediments supplied from the incoming plate lies off Kamaishi (Tsuru et al 2002;Huang and Zhao 2013). Weak interplate locking off Kamaishi is also implied by the degree of periodicity and the dominant period of slow slip (Uchida et al 2016). The absence of large earthquakes in the areas adjacent to the coring sites owing to these tectonic settings has likely facilitated the successive recording of the great-giant earthquakes in the cores.…”
Section: Sensitivity Of Turbidity Current Generation To Earthquake Grmentioning
confidence: 99%